2007
DOI: 10.1620/tjem.212.319
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Salivary Adenoid Cystic Carcinoma Associated with Perineural Invasion

Abstract: Adenoid cystic carcinoma (ACC) is a common salivary gland malignancy characterized by slow but progressive clinical course, proclivity for hematogenous spread and perineural invasion (PNI) that exhibits inherent resistance to complete surgical resection, systemic chemotherapy and conventional radiotherapy. The molecular alterations that underlie its PNI are poorly characterized. We report the combined use of laser capture microdissection (LCM) and high-throughput cDNA microarray to monitor in vivo gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
0
16
0
1
Order By: Relevance
“…The expression pattern and the quantitative expression level of CD146 were validated by quantitative real‐time polymerase chain reaction (PCR) and immunohistochemistry. That means CD146 may play a potential important role in the pathobiology of ACC associated with PNI (19). So, we hypothesized that knockdown of CD146 would inhibit in vitro PNI on ACC‐M cell.…”
Section: Introductionmentioning
confidence: 99%
“…The expression pattern and the quantitative expression level of CD146 were validated by quantitative real‐time polymerase chain reaction (PCR) and immunohistochemistry. That means CD146 may play a potential important role in the pathobiology of ACC associated with PNI (19). So, we hypothesized that knockdown of CD146 would inhibit in vitro PNI on ACC‐M cell.…”
Section: Introductionmentioning
confidence: 99%
“…In SACC, a recent study suggested that Notch-4 activation contributes to SACC metastasis (24). In our previous microarray study, Notch-4 was found to play a potential important role in the pathobiology of SACC associated with PNI (25). Thus, we tested our hypothesis on whether knockdown of Notch-4 by short hairpin RNA (shRNA) inhibits the in vitro proliferation and PNI in ACC-M cells.…”
Section: Lentiviral-mediated Gene Silencing Of Notch-4 Inhibits In VImentioning
confidence: 97%
“…The upregulated expression of COX‐2 and anti‐apoptotic protein Bcl2 in the luminal cells of pleomorphic adenoma was linked to tumor pathogenesis. A study was undertaken to analyze gene expression in adenoid cystic carcinoma (AdCC) to correlate it to perineural invasion by microdissecting cancer cells close to the nerve and distant from the nerve (Chen et al , ). This study implicated several novel genes responsible for perineural invasion in AdCC like melanoma cell adhesion molecule (MCAM), amphiregulin (AREG), meningioma expressed antigen 6 (MGEA6), N‐terminal caspase recruitment domain 12 (CARD12), peripheral myelin protein 22 (PMP22), taxol resistance‐associated gene 3 (TRAG3), MMP‐7, and nuclear transport factor 4 (NTF4) gene (Chen et al , ).…”
Section: Lcm For Integrated Oral Biosciencesmentioning
confidence: 99%
“…A study was undertaken to analyze gene expression in adenoid cystic carcinoma (AdCC) to correlate it to perineural invasion by microdissecting cancer cells close to the nerve and distant from the nerve (Chen et al , ). This study implicated several novel genes responsible for perineural invasion in AdCC like melanoma cell adhesion molecule (MCAM), amphiregulin (AREG), meningioma expressed antigen 6 (MGEA6), N‐terminal caspase recruitment domain 12 (CARD12), peripheral myelin protein 22 (PMP22), taxol resistance‐associated gene 3 (TRAG3), MMP‐7, and nuclear transport factor 4 (NTF4) gene (Chen et al , ). The authors found that melanoma‐associated gene (MAGE) family proteins (A2, A3, A4, and A9) and TRAG3, which cause DNA demethylation, are downregulated in AdCC with perineural invasion (Chen et al , ).…”
Section: Lcm For Integrated Oral Biosciencesmentioning
confidence: 99%